2020
DOI: 10.3390/brainsci10070459
|View full text |Cite
|
Sign up to set email alerts
|

“No Pain No Gain”: Evidence from a Parcel-Wise Brain Morphometry Study on the Volitional Quality of Elite Athletes

Abstract: Volition is described as a psychological construct with great emphasis on the sense of agency. During volitional behavior, an individual always presents a volitional quality, an intrapersonal trait for dealing with adverse circumstances, which determines the individual’s persistence of action toward their intentions or goals. Elite athletes are a group of experts with superior volitional quality and, thereby, could be regarded as the natural subject pool to investigate this mental trait. The purpose of this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…regions of the brain compared to healthy controls (Gaist et al, 2018;Khundrakpam et al, 2017), whereas retired athletes exposed to years of head impacts show cortical thinning compared to controls (Koerte et al, 2016;Wei et al, 2020). In our choking group, we observed significant increases in cortical thickness in the areas that are important for visual processing (e.g., parietal lobule and lateral occipital gyrus), working memory (e.g., middle frontal gyrus), language (e.g., supramarginal gyrus), object recognition (e.g., fusiform gyrus), and motor control (e.g., precentral gyrus).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…regions of the brain compared to healthy controls (Gaist et al, 2018;Khundrakpam et al, 2017), whereas retired athletes exposed to years of head impacts show cortical thinning compared to controls (Koerte et al, 2016;Wei et al, 2020). In our choking group, we observed significant increases in cortical thickness in the areas that are important for visual processing (e.g., parietal lobule and lateral occipital gyrus), working memory (e.g., middle frontal gyrus), language (e.g., supramarginal gyrus), object recognition (e.g., fusiform gyrus), and motor control (e.g., precentral gyrus).…”
Section: Discussionmentioning
confidence: 99%
“…The direction of changes (thickening vs. thinning) often depends on the brain regions and the nature of the neurologic insults or conditions, such that an instance of cortical thickening does not necessarily indicate a healthier brain than cortical thinning (Fischl & Dale, 2000 ). For example, patients with autism spectrum disorders and migraine exhibit cortical thickening in many regions of the brain compared to healthy controls (Gaist et al., 2018 ; Khundrakpam et al., 2017 ), whereas retired athletes exposed to years of head impacts show cortical thinning compared to controls (Koerte et al., 2016 ; Wei et al., 2020 ). In our choking group, we observed significant increases in cortical thickness in the areas that are important for visual processing (e.g., parietal lobule and lateral occipital gyrus), working memory (e.g., middle frontal gyrus), language (e.g., supramarginal gyrus), object recognition (e.g., fusiform gyrus), and motor control (e.g., precentral gyrus).…”
Section: Discussionmentioning
confidence: 99%
“…Activity in the parietal lobe is often associated with movement observation (Buccino et al, 2001) and motor performance in elite athletes (Yarrow et al, 2009). Furthermore, in a recent study, the left parietal lobe was found to be associated with volitional qualities (Wei et al, 2020). Aerobic athletes may have greater willpower than anaerobic athletes because they need to perform relatively longer and harder exercises.…”
Section: Aerobic Capacity Endurance and Brain Plasticitymentioning
confidence: 99%
“…Strong brain plasticity appears in the first few years of life, but various factors throughout adulthood still affect the morphology of brain structure and function. Occupation is a key factor that shapes our brain, which is closely related to our daily life, and exerts a subtle and persistent influence on brain plasticity changes (Wang N. et al, 2017(Wang N. et al, , 2018Dottori et al, 2020;Wei et al, 2020;Wu et al, 2020). Some studies have shown that the complexity of brain organization is an effective biomarker that reflects the individual's brain health level (Goldberger et al, 2002), aging (Sokunbi et al, 2011), cardiovascular diseases (Richman and Moorman, 2000), the neural effects of drug use (Ferenets et al, 2007), etc.…”
Section: Introduction Entropy-based Complexity Of Brain Activitymentioning
confidence: 99%